Design and Development of a Geographic Information System for Historical Tourism Sites in Sumenep Regency Using the Location-Based Service Method - Zain Nur, Achmad; Puteri Nurul Ma'rifah; Wildan Surya Wijaya (Universitas PGRI Adi Buana Surabaya, 2025)
This study presents the development of a Web-based Geographic Information System (Web GIS) aimed at mapping historical tourism sites in Sumenep Regency. The system integrates Location-Based Services (LBS) to enhance the delivery of spatial information and support tourism promotion. A prototype-based methodology was used in designing and building the application, which includes planning, requirements analysis, system design, data collection, and testing. The system architecture was modeled using UML diagrams, including use case, activity, and entity-relationship diagrams to ensure functionality and data integrity. Spatial and attribute data were collected through literature reviews and transformed into an interactive web platform that allows users to search for and visualize historical tourism locations. The system supports administrative features for data input and updates, alongside public-facing features such as maps and visitor statistics. Testing was conducted using black-box methods to verify the system’s performance and reliability. The final output is a fully functional Web GIS platform that enhances public access to tourism information and assists local authorities in managing tourism data effectively. This research contributes to the advancement of digital tourism infrastructure and promotes cultural heritage visibility in the region.